COMMON CAUSES OF LIMITED MOUTH OPENING ANDITS MANAGEMENT APPROACH AMONG DENTISTS IN KARACHI - Humayun Kaleem Siddiqui et al (Baqai Journal of Health Sciences)
Limited mouth opening, which is also known as trismus or lockjaw, has a number of abeyant issues and its treatment depends on the major cause. The objective of this study is to figure out the common causes of limited mouth opening in Karachi and to ascertain the management approach for a patient with trismus. The level of awareness and skill amongst clinicians with reference to the management of patients with trismus has also been evaluated. About 300 dental clinicians were asked a group of questions by the help of a questionnaire. The survey was conducted amongst the public and private dental OPDs in Karachi. The questions have been asked to evaluate the level of awareness, diagnostic approach, and quality of management and care offered to the patients having trismus. The three most common causes of trismus according to the present study came out to be oral submucosal fibrosis (26.7%), infections (24.0%), and trauma (15.0%), respectively. The dentists have chosen different management approaches according to their field of specialization and case dependence such as physiological mouth opening exercises (50.7%), prescribing medications specially muscle relaxants (24.3%), incision on contracted oral mucosa (12.7%), correction of temporomandibular joint (TMJ) or bone deformity (7.7%), and intralesional corticosteroid therapy (4.7%). The study concluded that trismus can turn into a potentially life-threatening situation if misdiagnosed and managed improperly; therefore, special attention should be given to patients coming with any of the above-mentioned symptoms.